PENERAPAN METODE TEAM QUIZ DALAM MENINGKATKAN MOTIVASI DAN KEDISIPLINAN SISWA PADA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMPN 1 BAREBBO - Asraf, Muh; Fadli, Tzul; Sarea, Muh Syahrul (Atta'dib Jurnal Pendidikan Agama Islam, 2025)
The application of the Active Learning "Team Quiz" method in increasing students' learning motivation and disciplinary character in Islamic Religious Education and Character lessons in class VII.4 at SMP Negeri 1 Barebbo is the focus of the research. This research aims to increase learning motivation and disciplinary character by using the Active Learning "Team Quiz" method. This research uses the type of Classroom Action Research (PTK) and is carried out in two cycles. Cycle I was held on 15 November 2024 and cycle II on 23 November 2024 at SMP Negeri 1 Barebbo which is located in Apala Village, Barebbo District, Bone Regency, South Sulawesi Province. The research subjects were 27 students in class VII.4 consisting of 12 female students and 15 male students. Data collection techniques through observation, interviews and documentation. The resulting data was analyzed using descriptive statistical analysis techniques. The results obtained show an increase in students' learning motivation and disciplinary character after implementing the "Team Quiz" active learning method in PAI learning both in cycle I and cycle II. Indicators of increasing motivation to learn are feelings of joy/focus in learning and student participation in discussions, while indicators of disciplinary character are punctuality in entering learning and neatness and modesty in dress which reached up to 92.58%. Therefore, it can be concluded that students' learning motivation and disciplinary character by applying the "Team Quiz" active learning method in Islamic Religious Education and Character learning in class VII.4 SMPN 1 Barebbo has increased.